Analysis of MTH-System (Methylcyclohexane-Toluene-Hydrogen-System) for hydrogen production as fuel for power plants. (13th November 2020) - Zahid, Abdul Hannan; Amin, Naila; Nisar, Fahid; Saghir, Summaira
Abstract: The utilization of hydrogen (H2 ) gas as green energy fuel in power plants is a great challenge due to its storage, deployment and transportation. Herein, we propose a simulation based study of H2 fueled power plant by using Methylcyclohexane-Toluene-Hydrogen-System (MTH-System). A 266 MW gas turbine was selected and the performance of MTH-System for power plant was investigated. The process for methylcyclohexane (MCH) production was not discussed here. However, the conversion of MCH into gaseous H2 for power generation was discussed in detail. A sustainable process flow diagram (PFD) was developed. The heat integration b/w power plant and dehydrogenation reactor reveal that, minimum 70% MCH conversion is required to accomplish the heat demand of whole system. The effect of addition of H2 recycle stream to dehydrogenation reactor and combined cycle power plants was investigated. The sensitivity and economic analysis reveal 2291.4 $/kW capital cost based on dehydrogenation of MCH for power production and 0.186 $/kWh output electricity cost based on complete MTH-System. Highlights: MTH-System was used to produce hydrogen fuel for power production. A sustainable PFD of MTH-System based power plant was firstly developed. Minimum 70% MCH dehydrogenation was required for optimum heat requirement of system. Electricity production cost was competitive with other conventional technologies. MTH-System based power plant works well for gas turbine only.